The Impact of BMI and Hormonal Contraception on Menstrual Abnormalities: A Cross-Sectional Analysis - Firdaus Al-Farisy, Alexandria (Journal La Medihealtico, 2024)
Hormonal contraception and body mass index (BMI) have been linked to menstrual irregularities, yet the nature of this relationship remains unclear. A cross-sectional study was conducted among0020a sample of 138 women who were using hormonal contraception. Data was collected through self-administered questionnaires. The participants were grouped based on type and duration of hormonal contraception use (combined contraceptives and progestin contraception) and their BMI was calculated based on their height and weight measurements. Menstrual abnormalities were recorded through the participants' self-reported data. Data was analysed using descriptive statistics, chi-square tests, and logistic regression models. Results showed that there was a significant difference in menstrual abnormalities between different types of hormonal contraception p=0.021, OR=2.398, Women who used progestin only contraception had a higher risk of developing menstrual abnormalities than combined contraceptives. There was significance different of duration of use hormonal contraception with menstrual abnormalities p=0.037, OR=2.312 for a long duration (more than 1 years) compared to less than one year. Women with a higher BMI (greater than 25 kg/m2) p=0.038, OR=2.169 had a significant risk of developing menstrual abnormalities. The study concludes that the type and duration of hormonal contraception use and BMI play a significant role in the development of menstrual abnormalities. Women should be informed about the potential risks and benefits of different types of hormonal contraception and the importance of maintaining a healthy BMI. Healthcare providers should consider these factors when making recommendations for hormonal contraception.